Analysis of Scientific Publication Skills of Elementary School Teachers - Hartono Hartono; Sularmi Sularmi; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Universitas Sebelas Maret, 2019)
The purpose of the service is to train elementary school teachers to have the competence of Scientific Publication on Elementary Teachers in the City of Surakarta. In addition to training teachers, this service also aims to analyze teacher competencies in Scientific Publications on Elementary Teachers in Surakarta. The subject of this service is an elementary school teacher in the city of Surakarta. The method used in this service starts with Workshop, Practice, and Implementation. In conducting this training, the subjects were asked to take a test related to the preparation of articles and Scientific Publications. Analysis of the data used is pre-test and post-test. The result of this activity is that there is an increase in teacher's knowledge and understanding of the preparation of scientific articles and Scientific Publications.